Patterns of adjuvant treatment and survival outcomes in stage I uterine carcinosarcoma - Lori Cory; Colleen Brensinger; Robert A. Burger; Robert L. Giuntoli, II; Mark A. Morgan; Nawar Latif; Lilie L. Lin; Emily M. Ko (Elsevier, 2022)
Objective: To determine patterns in type and sequence of adjuvant treatment and associated differences in overall survival among women with Stage I uterine carcinosarcoma (UCS). Methods: Women with stage I UCS from 2000 to 2015 were identified through the National Cancer Institute's Surveillance, Epidemiology and End Results database linked to Medicare-based claims follow-up data through 2016. Data including demographics, co-morbidities, surgical procedure, surgical pathology and type and sequence of adjuvant treatment were collected. The primary study outcome was overall survival (OS) by type and sequence of adjuvant therapy. Cancer specific survival was also analyzed. Results: A total of 755 women with Stage I UCS were identified. Of these, 56.3% (n = 445) received adjuvant therapy, whereas 43.7% (n = 330) did not. In comparison to no adjuvant treatment, an overall survival benefit was noted with receipt of chemotherapy alone for women with Stage I disease (log rank p < 0.01). Pairwise comparisons did not show a benefit in OS of concurrent RT-chemo, sequential RT-chemo, or sequential chemo-RT, over chemotherapy alone (p > 0.05 for all). Likewise, radiation alone and no treatment were associated with worse OS compared to chemotherapy alone (p < 0.001 for both). Adjusted Cox regression models demonstrated an OS benefit only in the chemotherapy alone cohort for Stage I disease (HR 0.43 95% CI 0.32, 0.60, p < 0.0001), as well as for CSS (HR 0.41, 95 %CI 0.26, 0.62, p < 0.0001), compared to no treatment. Conclusions: In comparison to no adjuvant therapy, an overall survival and cancer-specific survival benefit was noted with receipt of chemotherapy alone in Stage I UCS.